The Relation Between the Credit Default Swap and Corporate Bond Market - Nilsson,Sofia; Sandahl,Isabelle (2018)
The European credit default swap (CDS) market has experienced noticeable changes and remarkably developed over the last decades. Today, the relation between the CDS and corporate bond market is a prominent topic in the financial literature. According to the arbitrage argument, the CDS spread equals the corresponding credit spread of a corporate bond. However, substantial deviations between the markets are found in the short run. Because of that, researchers try to grasp the importance of the CDS market in the context of the price discovery process of credit risk. To contribute to the literature, this study attempts to explain the gap between the markets for 84 European companies with different credit ratings over the period 2013 to 2017. Credit ratings are added as an additional dimension as they contribute with valuable information and thus have a strong impact on capital markets. By dividing the sample into subsamples, the results for different credit rated companies are analyzed. The results suggest that the arbitrage argument do not hold in the short run since credit risk at the CDS market are found to be overestimated or underestimated in relation to the corporate bond market. Moreover, the sensitivity to structural and market factors are found to differ between the rating groups.
Keywords: Credit Default Swap; Corporate Bond Market; Credit Risk; Arbitrage Argument; Credit Ratings